Tradisi Kalo Sara pada Masyarakat Tolaki di Kabupaten Konawe, Provinsi Sulawesi Tenggara - Jamil Jamil; La Taena La Taena; Abdul Alim; Aso La Aso (Universitas Halu Oleo, 2023)
Abstract: This study aims to describe and analyze the meaning of kalo sara tradition in Tolaki community in Konawe Regency, Southeast Sulawesi Province because kalo sara tradition is one of the local wisdoms for the Tolaki community which is used to resolve conflicts. This research is a qualitative research, and was carried out in Konawe Sub-district, Konawe Regency, Southeast Sulawesi Province. Source of data consists of primary data and secondary data. To gather information, both in the form of primary data and secondary data, three techniques are used, namely: (1) observation, in-depth interviews, and documentation study. The results of this study showed that the customary meaning of kalo sara in the Tolaki community in Konawe Sub-district, Konawe Regency are as follows: The meaning of the tradition of kalo sara in the Tolaki community in Konawe Sub-district is as follows: (1) The tools used are still traditional in nature which have been passed down from generation to generation to generation. The tool is a woven and sacred container, so to get the basic ingredients, you have to do it with good and lucky effort and luck. (2) Siwole uwa is a kind of platter woven from palm fronds (or rema) with certain motifs. In Tolaki language it is called I nana (plait) and means the basis of honor. In addition, siwole mbatohu was an expression of regional politics during the leadership of Mokole Tebawo or Sangia Inato in the 17th century. The three ends of the rattan, two of which are hidden in a knot, are closely related to the word wisdom. Meanwhile, the winding of three rattan threads has a meaning as a unit of social stratification of the Tolaki people. (4) O bite (siri leaf) is a vine, but not a parasite or parasite. so it doesn't damage the tree where it's vines. The siri leaf is a symbol of the heart and has been used since ancient times to show spirituality, emotion, morals. (5) I nea (areca nut) for the Tolaki people has a very high value in customs. Inea (areca nut) is a symbol of the lineage of people who have good character, are honest, and have a high degree. and (6) Lopa-lopa niwule is a symbol of acceptance from both parties consisting of lime (o wule) which means white heart and sincerity but sirit has a bad side, that the lime contains a chemical reaction that can destroy anything, assuming human nature when it is in good condition it will look white and clean, but when it is hurt or injured it will have a bad impact.Keywords: Kalo sara, tradition, Tolaki community